2018
DOI: 10.1177/1071100718790489
|View full text |Cite
|
Sign up to set email alerts
|

Structures at Risk During Percutaneous Screw Fixation for Talonavicular Fusion

Abstract: Based on these results, we recommend a careful dissection be performed prior to percutaneous screw insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This has been reported before. 1,6 Third, our specimen did not have any pathologies or gross deformities. However, most patients requiring talonavicular fusion are fairly arthritic, so we cannot generalize the findings to preparation of a stiff, advanced osteoarthritic joint with osteophytes.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This has been reported before. 1,6 Third, our specimen did not have any pathologies or gross deformities. However, most patients requiring talonavicular fusion are fairly arthritic, so we cannot generalize the findings to preparation of a stiff, advanced osteoarthritic joint with osteophytes.…”
Section: Discussionmentioning
confidence: 96%
“…The average branching position of SPN was 7.5 cm distal to the ankle joint, so it was recommended that incision for arthroscopic portals be made more proximal to reduce risk of damaging the nerve. 2 Lee et al, 6 in their study of 10 cadaveric feet, found difficulty in their screw placement at the edge of the dorsal navicular between medial and intermediate cuneiforms due to the branching pattern of SPN. In the one instance the DPN was contacted, it was transected, and previous literature shows potential concern for this scenario as well.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations